Reconsidering the debate relating to the proposals for the regulation of cryptocurrencies in South Africa - De Sousa, Michaella Alexandrine (University of the Witwatersrand, Johannesburg, 2023)
Words cannot express my gratitude to my supervisor, Professor Herbert Kawadza for his vital patience and feedback. His guidance and vast knowledge in commercial and banking law was the main reason I hoped to have him as my supervisor for the completion of my LLM Research Report, without him I would still be lost in my drafting. I am extremely grateful for the guidance and encouragement of my two very close colleagues and mentors, Daven Dass and Alicia Raymond, their encouragement and conversation pushed me through writer’s block and self-doubt. I certainly could not have undertaken this journey without my strong support system and the most important people in my life, my father, Rui de Sousa; my sister, Claudia de Sousa; and partner, Nicholas Elliott. Their belief in me and ongoing patience in reading and rereading every iteration of this LLM Research Report will always be appreciated. This degree would never have been completed without them. As the adage goes, I am because they are, and I will always be indebted to them. Lastly, this LLM degree is for my late mother, Carla de Sousa, without her guidance and belief I would not be where I am now, and I will always be grateful to her
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg
Keywords: Crypto; Bitcoin; Investors; Crypto assets; South African Government; Cryptocurrencies; UCTD; SDG-8: Decent work and economic growth